THE POLITICAL FRAMING OF THE 2024 CHINA-INDONESIA JOINT STATEMENT - Maulaya, Mahbi (Global: Jurnal Politik Internasional, 2025)
Political leaders always carefully choose what to say and how to state it, as all words count for influencing the public, explicitly or implicitly. Eventually, the ideas framed in a political statement are best understood contextually rather than merely textually. After Prabowo Subianto, the president of Indonesia, visited China in November 2024, both countries released a controversial joint statement. This article aims to analyse the political frames observable in the 2024 China-Indonesia joint statement with a discourse analysis method. The article found five political frames in the statement: 1) Indonesia agrees to China’s vision of global order; 2) China has a positive image as a trustworthy and non-discriminatory power; 3) Indonesia is open to intimate defence cooperation with China; 4) Indonesia aligns with and is on China’s side; 5) Indonesia supports China’s critical domestic and international ambition. With these findings, this paper argues that the joint statement is in favour of China politically and costs Indonesia its political image as a free, active, and democratic country.